PEMBELAJARAN PENGENALAN LAFADZ TAJWID UNTUK SISWA MADRASAH BERBASIS MULTIMEDIA PADA MTsN 1 KOTA BEKASI - Siti Nurajizah; Ervan Aziz (Jurnal Mantik Penusa, 2018)
For students Madrasah Tsanawiyah Negeri 1 Bekasi City especially new learners to rise the next level sometimes lesson material delivered is not easy to understand or often learners feel bored and lazy to understand and read books. Though learning will be fun if we can use interactive media methods. Learning media in the form of interactive animation is used as one of the solutions in the delivery of material for teaching and learning activities, the discussion about learning to know lafazd tajwid so that learners easily absorb and understand the material delivered by teachers or teachers. With the media of learning that is interesting for learners such as interactive animation is expected to improve learning achievement and as a fun learning media. The software used to create this interactive animation is Adobe Flash CS5.